Effectiveness of tobacco control television advertisements with different types of emotional content on tobacco use in England, 2004–2010. Issue 1 (18th July 2014) - Sims, M; Langley, T; Lewis, S; Richardson, S; Szatkowski, L; McNeill, A; Gilmore, A B
Abstract : Aim: To examine the effects of tobacco control television advertisements with positive and negative emotional content on adult smoking prevalence and cigarette consumption. Design: Analysis of monthly cross-sectional surveys using generalised additive models. Setting: England. Participants: 60 000 adults aged 18 years or over living in England and interviewed in the Opinions and Lifestyle Survey from 2004 to 2010. Measurements: Current smoking status, daily cigarette consumption, tobacco control gross rating points (GRPs—a measure of per capita advertising exposure), cigarette costliness, concurrent tobacco control policies, sociodemographic variables. Results: After adjusting for cigarette costliness, other tobacco control policies and individual characteristics, we found that a 400-point increase in positive emotive GRPs was associated with 7% lower odds of smoking (odds ratio (OR) 0.93, 95% CI 0.87 to 0.98) 1 month later and a similar increase in negative emotive GRPs was significantly associated with 4% lower odds of smoking (OR 0.96, 95% CI 0.92 to 0.999) 2 months later. An increase in negative emotive GRPs from 0 to 400 was also associated with a significant 3.3% (95% CI 1.1 to 5.6) decrease in average cigarette consumption. There was no evidence that the association between positive emotive GRPs and the outcomes differed depending on the intensity of negative emotive GRPs (and vice versa). Conclusions: This is the first study to explore the effects of campaigns with different types of emotive content on adult smoking prevalence and consumption. It suggests that both types of campaign (positive and negative) are effective in reducing smoking prevalence, whereas consumption among smokers was only affected by campaigns evoking negative emotions.